Effects of ta’awun in sustaining ethical and socially responsible Managers for sustainable competitive advantage - Mhd. Sarif, Suhaimi (Zes Rokman Resources (2131022-P), 2018)
In competitive market, having sustainable competitive advantage is necessary to remain competitive and survive. The process of creating and sustaining competitive advantage is integrative, interactive and comprehensive among stakeholders. Ta’awun or Tawhidic driven spiritual strategic cooperation from Islamic perspectives enables the process to produce ethical and socially responsible. Integration through scope of organisational operations through vertical and horizontal integration strengthens organisational strategies on sustainable manner. The integration theory allows for strategic cooperation or ta’awun to achieve sustainable competitive advantage. Based on the literature review pertaining to strategic cooperation and ta’awun, there are some effects ta’awun in making managers to be ethical and responsible. Thus, this study aimed to explore the effects of ta’awun in sustaining ethical and socially responsible managers. Since this study is exploratory into the reality of managers, the study used qualitative method through personal interview with marketing and sales managers in Malaysia to solicit their views on the effects of being mutual co--operative or ta’awun with stakeholders in sustaining performance and competitive advantage. Validity, reliability and credibility of the study and the results have been conducted within qualitative research methodology. The results of the study showed that the effects of ta’awun are in a few factors, namely social integration with social contract, norms and belief; organisational structure and process; management policies, systems and resources; and continuous (fastaqim) training for ethical (tarbiyyah khuluq) and socially responsible practices (khuluq bil‘amal ijtima’ie). The implications for practice are to institutionalise standard operating procedure (SOP), code of conduct, and regular education for managerial ethics. The results of the study is not to generalise or confirming of any theory, but to understand the situation of the event from the real context of the situation. The implications of practice and policy of organisations are in the code of conduct and training programmes to include continuous education and job training. As for theory, this study contributed to the contemporary theory of normative ethics from Islamic perspective of ta’awun, spiritual or soul-based strategic cooperation and alliances. Future studies should use mixed methods or case study method to include more views and insights from many stakeholders. Keywords: Ta’awun, Business ethics, Social responsibility.